CGRP measurements in human plasma – a methodological study - Meßlinger, Karl; Vogler, Birgit; Kuhn, Annette; Sertel-Nakajima, Julika; Frank, Florian; Broessner, Gregor (Cephalalgia, 2021)
Background: Calcitonin gene-related peptide plasma levels have frequently been determined as a biomarker for primary headaches. However, published data is often inconsistent resulting from different methods that are not precisely described in most studies. Methods: We applied a well-proven enzyme-linked immunosorbent assay to measure calcitonin gene-related peptide concentrations in human blood plasma, we modified parameters of plasma preparation and protein purification and used calcitonin gene-related peptide-free plasma for standard solutions, which are described in detail. Results: Calcitonin gene-related peptide levels are stable in plasma with peptidase inhibitors and after deep-freezing. Calcitonin gene-related peptide standard solutions based on synthetic intercellular fluid or pooled plasma with pre-absorbed calcitonin gene-related peptide influenced the measurements but yielded both comprehensible results. In a sample of 56 healthy subjects the calcitonin gene-related peptide plasma levels varied considerably from low (<50 pg/mL) to very high (>500 pg/mL) values. After a 12-hour exposure of these subjects to normobaric hypoxia the individual calcitonin gene-related peptide levels remained stable. Conclusion: Buffering with peptidase inhibitors and immediate freezing or processing of plasma samples is essential to achieve reliable measurements. Individuals show considerable differences and partly high calcitonin gene-related peptide plasma levels without detectable pathological reason. Thus plasma measurements are suited particularly to follow calcitonin gene-related peptide levels in longitudinal studies. The use of data for this study was approved by the Ethics Committee of the Medical University of Innsbruck (https://www.i-med.ac.at/ethikkommission/; EK Nr: 1242/2017).
CRIS-Team Scopus Importer:2021-07-30
Keywords: blood plasma; Calcitonin gene-related peptide; enzyme-linked immunosorbent assay; normobaric hypoxia

CGRP outflow into jugular blood and cerebrospinal fluid and permeance for CGRP of rat dura mater - Risch, Miriam; Vogler, Birgit; Dux, Maria; Meßlinger, Karl (Journal of Headache and Pain, 2021)
Background: Calcitonin gene-related peptide (CGRP) is released from activated meningeal afferent fibres in the cranial dura mater, which likely accompanies severe headache attacks. Increased CGRP levels have been observed in different extracellular fluid compartments during primary headaches such as migraine but it is not entirely clear how CGRP is drained from the meninges. Methods: We have used an in vivo preparation of the rat to examine after which time and at which concentration CGRP applied onto the exposed parietal dura mater appears in the jugular venous blood and the cerebrospinal fluid (CSF) collected from the cisterna magna. Recordings of meningeal (dural) and cortical (pial) blood flow were used to monitor the vasodilatory effect of CGRP. In a new ex vivo preparation we examined how much of a defined CGRP concentration applied to the arachnoidal side penetrates the dura. CGRP concentrations were determined with an approved enzyme immunoassay. Results: CGRP levels in the jugular plasma in vivo were slightly elevated compared to baseline values 5-20 min after dural application of CGRP (10 μM), in the CSF a significant three-fold increase was seen after 35 min. Meningeal but not cortical blood flow showed significant increases. The spontaneous CGRP release from the dura mater ex vivo was above the applied low concentration of 1 pM. CGRP at 1 nM did only partly penetrate the dura. Conclusions: We conclude that only a small fraction of CGRP applied onto the dura mater reaches the jugular blood and, in a delayed manner, also the CSF. The dura mater may constitute a barrier for CGRP and limits diffusion into the CSF of the subarachnoidal space, where the CGRP concentration is too low to cause vasodilatation.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Calcitonin gene-related peptide; Cerebrospinal fluid; Jugular plasma; Meningeal blood flow; Primary headaches

Fremanezumab, an anti-CGRP monoclonal antibody, reduces stimulated CGRP release from rat cranial dura mater - Vogler, Birgit; Nakajima, Julika; Mackenzie, Kimberly; Stratton, Jennifer; Meßlinger, Karl (CEPHALALGIA, 2019)
CRIS-Team WoS Importer:2019-11-01

Glycerol Trinitrate Acts Downstream of Calcitonin Gene-Related Peptide in Trigeminal Nociception—Evidence from Rodent Experiments with Anti-CGRP Antibody Fremanezumab - Benedicter, Nicola; Vogler, Birgit; Kuhn, Annette; Schramm, Jana; Mackenzie, Kimberly D.; Stratton, Jennifer; Dux, Mária; Meßlinger, Karl (Cells, 2024)
Calcitonin gene-related peptide (CGRP) and nitric oxide (NO) have been recognized as important mediators in migraine but their mechanisms of action and interaction have not been fully elucidated. Monoclonal anti-CGRP antibodies like fremanezumab are successful preventives of frequent migraine and can be used to study CGRP actions in preclinical experiments. Fremanezumab (30 mg/kg) or an isotype control monoclonal antibody was subcutaneously injected to Wistar rats of both sexes. One to several days later, glyceroltrinitrate (GTN, 5 mg/kg) mimicking nitric oxide (NO) was intraperitoneally injected, either once or for three consecutive days. The trigeminal ganglia were removed to determine the concentration of CGRP using an enzyme-linked immunosorbent assay (ELISA). In one series of experiments, the animals were trained to reach an attractive sugar solution, the access to which could be limited by mechanical or thermal barriers. Using a semi-automated registration system, the frequency of approaches to the source, the residence time at the source, and the consumed solution were registered. The results were compared with previous data of rats not treated with GTN. The CGRP concentration in the trigeminal ganglia was generally higher in male rats and tended to be increased in animals treated once with GTN, whereas the CGRP concentration decreased after repetitive GTN treatment. No significant difference in CGRP concentration was observed between animals having received fremanezumab or the control antibody. Animals treated with GTN generally spent less time at the source and consumed less sugar solution. Without barriers, there was no significant difference between animals having received fremanezumab or the control antibody. Under mechanical barrier conditions, all behavioral parameters tended to be reduced but animals that had received fremanezumab tended to be more active, partly compensating for the depressive effect of GTN. In conclusion, GTN treatment seems to increase the production of CGRP in the trigeminal ganglion independently of the antibodies applied, but repetitive GTN administration may deplete CGRP stores. GTN treatment generally tends to suppress the animals’ activity and increase facial sensitivity, which is partly compensated by fremanezumab through reduced CGRP signaling. If CGRP and NO signaling share the same pathway in sensitizing trigeminal afferents, GTN and NO may act downstream of CGRP to increase facial sensitivity.
CRIS-Team Scopus Importer:2024-04-26
Keywords: calcitonin gene-related peptide; CGRP concentration; CGRP release; fremanezumab; glycerol trinitrate; migraine pain; monoclonal antibody; rat

High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Mária; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2019)
Background: The α1-adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. Methods: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. Results: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. Conclusions: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. Significance: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
CRIS-Team Scopus Importer:2019-12-03

High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Maria; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2020)
BACKGROUND: The α1 -adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. METHODS: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. RESULTS: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. CONCLUSIONS: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. SIGNIFICANCE: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
EVALuna2:213473

Meningeal blood flow is controlled by H2 S-NO crosstalk activating a HNO-TRPA1-CGRP signalling pathway - Dux, Maria; Will, Christine; Vogler, Birgit; Filipovic, Milos; Meßlinger, Karl (British Journal of Pharmacology, 2016)
BACKGROUND AND PURPOSE: Meningeal blood flow is controlled by CGRP released from trigeminal afferents and NO mainly produced in arterial endothelium. The vasodilator effect of NO may be due to the NO-derived compound, nitroxyl (HNO), generated through reaction with endogenous H2 S. We investigated the involvement of HNO in CGRP release and meningeal blood flow. EXPERIMENTAL APPROACH: Blood flow in exposed dura mater of rats was recorded by laser Doppler flowmetry. CGRP release from the dura mater in the hemisected rat head was quantified using an elisa. NO and H2 S were localized histochemically with specific sensors. KEY RESULTS: Topical administration of the NO donor diethylamine-NONOate increased meningeal blood flow by 30%. Pretreatment with oxamic acid, an inhibitor of H2 S synthesis, reduced this effect. Administration of Na2 S increased blood flow by 20%, an effect abolished by the CGRP receptor antagonist CGRP8-37 or the TRPA1 channel antagonist HC030031 and reduced when endogenous NO synthesis was blocked. Na2 S dose-dependently increased CGRP release two- to threefold. Co-administration of diethylamine-NONOate facilitated CGRP release, while inhibition of endogenous NO or H2 S synthesis lowered basal CGRP release. NO and H2 S were mainly localized in arterial vessels, HNO additionally in nerve fibre bundles. HNO staining was lost after treatment with L-NMMA and oxamic acid. CONCLUSIONS AND IMPLICATIONS: NO and H2 S cooperatively increased meningeal blood flow by forming HNO, which activated TRPA1 cation channels in trigeminal fibres, inducing CGRP release. This HNO-TRPA1-CGRP signalling pathway may be relevant to the pathophysiology of headaches.
EVALuna2:32819

Petasin and isopetasin reduce CGRP release from trigeminal afferents indicating an inhibitory effect on TRPA1 and TRPV1 receptor channels - Kleeberg-Hartmann, Johanna; Vogler, Birgit; Meßlinger, Karl (Journal of Headache and Pain, 2021)
Background: Butterbur root extract with its active ingredients petasin and isopetasin has been used in the prophylactic treatment of migraine for years, while its sites of action are not completely clear. Calcitonin gene-related peptide (CGRP) is known as a biomarker and promoting factor of migraine. We set out to investigate the impact of petasins on the CGRP release from trigeminal afferents induced by activation of the calcium conducting transient receptor potential channels (TRPs) of the subtypes TRPA1 and TRPV1. Methods: We used well-established in vitro preparations, the hemisected rodent skull and dissected trigeminal ganglia, to examine the CGRP release from rat and mouse cranial dura mater and trigeminal ganglion neurons, respectively, after pre-incubation with petasin and isopetasin. Mustard oil and capsaicin were used to stimulate TRPA1 and TRPV1 receptor channels. CGRP concentrations were measured with a CGRP enzyme immunoassay. Results: Pre-incubation with either petasin or isopetasin reduced mustard oil- and capsaicin-evoked CGRP release compared to vehicle in an approximately dose-dependent manner. These results were validated by additional experiments with mice expressing functionally deleted TRPA1 or TRPV1 receptor channels. Conclusions: Earlier findings of TRPA1 receptor channels being involved in the site of action of petasin and isopetasin are confirmed. Furthermore, we suggest an important inhibitory effect on TRPV1 receptor channels and assume a cooperative action between the two TRP receptors. These mechanisms may contribute to the migraine prophylactic effect of petasins.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Butterbur; CGRP; Isopetasin; Migraine; Petasin; TRPA1; TRPV1

Role of transient receptor potential ankyrin 1 receptors in rodent models of meningeal nociception - Experiments in vitro - Denner, Ann Catherine; Vogler, Birgit; Meßlinger, Karl; De Col, Roberto (European Journal of Pain, 2017)
BACKGROUND: The TRP channel ankyrin type 1 (TRPA1) is a nonselective cation channel known to be activated by environmental irritants, cold and endogenous mediators of inflammation. Activation of TRPA1 in trigeminal afferents innervating meningeal structures has recently been suggested to be involved in the generation of headaches. METHODS: Two in vitro models of meningeal nociception were employed using the hemisected rodent head preparation, (1) recording of single meningeal afferents and (2) release of calcitonin gene-related peptide (CGRP) from the cranial dura mater. The role of TRPA1 was examined using the TRPA1 agonists acrolein and mustard oil (MO). BCTC, an inhibitor of TRP vanilloid type 1 receptor channels (TRPV1), and the TRPA1 inhibitor HC030031 as well as mice with genetically deleted TRPA1 and TRPV1 proteins, were used to differentiate between effects. RESULTS: Acrolein did not cause discharge activity in meningeal Aδ- or C-fibres but increased the electrical activation threshold. Acrolein was also effective in releasing CGRP from the dura of TRPV1-/-but not of TRPA1-/-mice. MO increased the discharge activity of afferent fibres from rat as well as C57 wild-type and TRPA1-/-but not TRPV1-/-mice. The effect was higher in C57 compared to TRPA1-/-mice. CONCLUSION: Sole TRPA1 receptor channel activation releases CGRP and increases the activation threshold of meningeal afferents but does not generate propagated activity, and so would be capable of causing local effects like vasodilatation but not pain generation. In contrast, combined TRPA1 and TRPV1 activation may be rather pronociceptive supporting headache generation. SIGNIFICANCE: Sole activation of TRPA1 receptor channels increases the activation threshold but does not cause propagated action potentials in meningeal afferents. TRPA1 agonists cause CGRP release from rodent dura mater. Peripheral TRPA1 receptors may have a pronociceptive function in trigeminal nociception only in combination with TRPV1.
EVALuna2:33348

Semi-Automated Recording of Facial Sensitivity in Rat Demonstrates Antinociceptive Effects of the Anti-CGRP Antibody Fremanezumab - Benedicter, Nicola; Meßlinger, Karl; Vogler, Birgit; Mackenzie, Kimberly D.; Stratton, Jennifer; Friedrich, Nadine; Dux, Mária (Neurology International, 2023)
Migraine pain is frequently accompanied by cranial hyperalgesia and allodynia. Calcitonin gene-related peptide (CGRP) is implicated in migraine pathophysiology but its role in facial hypersensitivity is not entirely clear. In this study, we investigated if the anti-CGRP monoclonal antibody fremanezumab, which is therapeutically used in chronic and episodic migraines, can modify facial sensitivity recorded by a semi-automatic system. Rats of both sexes primed to drink from a sweet source had to pass a noxious mechanical or heat barrier to reach the source. Under these experimental conditions, animals of all groups tended to drink longer and more when they had received a subcutaneous injection of 30 mg/kg fremanezumab compared to control animals injected with an isotype control antibody 12–13 days prior to testing, but this was significant only for females. In conclusion, anti-CGRP antibody, fremanezumab, reduces facial sensitivity to noxious mechanical and thermal stimulation for more than one week, especially in female rats. Anti-CGRP antibodies may reduce not only headache but also cranial sensitivity in migraineurs.
CRIS-Team Scopus Importer:2023-07-28
Keywords: behavioral model; calcitonin gene-related peptide; fremanezumab; mechanical sensitivity; migraine symptoms; monoclonal antibody; thermal sensitivity

The Anti-Calcitonin Gene-Related Peptide (Anti-CGRP) Antibody Fremanezumab Reduces Trigeminal Neurons Immunoreactive to CGRP and CGRP Receptor Components in Rats - Vogler, Birgit; Kuhn, Annette; Mackenzie, Kimberly D.; Stratton, Jennifer; Dux, Mária; Meßlinger, Karl (International Journal of Molecular Sciences, 2023)
Treatment with the anti-CGRP antibody fremanezumab is successful in the prevention of chronic and frequent episodic migraine. In preclinical rat experiments, fremanezumab has been shown to reduce calcitonin gene-related peptide (CGRP) release from trigeminal tissues and aversive behaviour to noxious facial stimuli, which are characteristic pathophysiological changes accompanying severe primary headaches. To further decipher the effects of fremanezumab that underlie these antinociceptive effects in rats, immunohistochemistry and ELISA techniques were used to analyse the content and concentration of CGRP in the trigeminal ganglion, as well as the ratio of trigeminal ganglion neurons which are immunoreactive to CGRP and CGRP receptor components, 1–10 days after subcutaneous injection of fremanezumab (30 mg/kg) compared to an isotype control antibody. After fremanezumab treatment, the fraction of trigeminal ganglion neurons which were immunoreactive to CGRP and the CGRP receptor components calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1 (RAMP1) was significantly lowered compared to the control. The content and concentration of CGRP in trigeminal ganglia were not significantly changed. A long-lasting reduction in CGRP receptors expressed in trigeminal afferents may contribute to the attenuation of CGRP signalling and antinociceptive effects of monoclonal anti-CGRP antibodies in rats.
CRIS-Team Scopus Importer:2023-09-15
Keywords: calcitonin gene-related peptide; CGRP release; fremanezumab; migraine pain; monoclonal antibody; rat; trigeminal ganglion

The Anti-CGRP Antibody Fremanezumab Lowers CGRP Release from Rat Dura Mater and Meningeal Blood Flow - Dux, Maria; Vogler, Birgit; Kuhn, Annette; Mackenzie, Kimberly D.; Stratton, Jennifer; Meßlinger, Karl (Cells, 2022)
Monoclonal antibodies directed against the neuropeptide calcitonin gene-related peptide (CGRP) belong to a new generation of therapeutics that are effective in the prevention of migraine. CGRP, a potent vasodilator, is strongly implicated in the pathophysiology of migraine, but its role remains to be fully elucidated. The hemisected rat head preparation and laser Doppler flowmetry were used to examine the effects on CGRP release from the dura mater and meningeal blood flow of the subcutaneously injected anti-CGRP monoclonal antibody fremanezumab at 30 mg/kg, when compared to an isotype control antibody. Some rats were administered glycerol trinitrate (GTN) intraperitoneally to produce a migraine-like sensitized state. When compared to the control antibody, the fremanezumab injection was followed by reduced basal and capsaicin-evoked CGRP release from day 3 up to 30 days. The difference was enhanced after 4 h of GTN application. The samples from the female rats showed a higher CGRP release compared to that of the males. The increases in meningeal blood flow induced by acrolein (100 mu M) and capsaicin (100 nM) were reduced 13-20 days after the fremanezumab injection, and the direct vasoconstrictor effect of high capsaicin (10 mu M) was intensified. In conclusion, fremanezumab lowers the CGRP release and lasts up to four weeks, thereby lowering the CGRP-dependent meningeal blood flow. The antibody may not only prevent the released CGRP from binding but may also influence the CGRP release stimulated by noxious agents relevant for the generation of migraine pain.
CRIS-Team WoS Importer:2022-06-24